A patchy particle model for C-S-H formation. (February 2022) - Prabhu, Achutha; Dolado, Jorge S.; Koenders, Eddie A.B.; Zarzuela, Rafael; Mosquera, María J.; Garcia-Lodeiro, Ines; Blanco-Varela, María Teresa
Abstract: The composition and structure of Calcium-Silicate-Hydrate (C-S-H) phases depends on various reaction parameters leading to its formation. Molecular Dynamic simulation studies probing the formation and structure of C-S-H are generally computationally expensive and can reach only very short time scales. Herein, we propose a coarse graining approach to model the formation of C-S-H, using patchy particles and a modified Patchy Brownian Cluster Dynamics algorithm. The simulations show that patchy particle systems can recover the qualitative kinetic evolution of C-S-H formation, and the obtained final structures were comparable to previously reported molecular dynamics studies and experiments. The model was extended to study the effect of water in the polymerization of tetraethoxysilane oligomers, the principal component of an impregnation treatment for deteriorated concrete surfaces. The intermediate system properties predicted by the simulations, such as viscosity and gel time, and structure were found to be well in accordance with the tailored experiments.